Aspectos politicos e institucionais da administração metropolitana no Brasil: o caso de Belo Horizonte - Matos, Josadac Figueira de (1982)
This monograph analyzes the political and institutional hindrances to the implementation and survival of a planning and administrative organization located in the metropolitan region of Belo Horizonte, since ~he inceution of the first ideas which have identified the need for an urban ulan for the region UP to the creation of a public authority, namely the Su perintend~ncia de Desenvolvimento Metrouolitano - PLAMBEL. The surviving and adautative mechanisms necessary to face an often hostile milieu have been stressed herein. The object of this study is an agency whose area of activities is a metrouolitan region. In view of this fact, the author found it convenient, prior to beginning an analysis of the previous background and accomplishments, to determine some concepts which were more usual among those concerned with metropolitan regions, aiming at identifying the parameters, variables and characteristics used in Brazil for a definition of metropolitan regions. Therefore the first uart of the uaper is entirely focused upon the pertinent theoretical and institutional reference background, including a discussion of the forms found to exist in other countries where metropolitan·phenomenum has received more attention on the Dart of the uublic power, who has thus being attempting to eliminate or minimize the distorting ef fects of metrouolitanizing. After analyzing the organization and its major accomplishments, including those uerformed before its formal implementation,the author concludes that, considering the current irreversible situation of metrouolitan planning and administrative agencie~ it can be expected that PLAMBEL will impose itself as anindispensable organization which will act as a planning and coordinating instrument for governamental action in the metropolitan area of Belo Horizonte. The author stresses, also, the need for a reliable association between PLAMBEL and the municipalities 50 that metropolitan interests, as defined in the monograph, can effectively overcome the interests of local governments and the sectorial interests for other governmental agencies which eventually migth try to operate without taking into consideration the overall plans for the regi9n.